Laporan Kasus : Pasien Perempuan 25 Tahun dengan Rhinitis Alergi - Muchammad Aqsa Enrico Ricardo; Mukhlis Imanto (CV. Jasa Sukses Abadi, 2026)
Allergic rhinitis is an immunoglobulin E mediated inflammation of the nasal mucosa characterized by recurrent sneezing, nasal obstruction, rhinorrhea, and ocular symptoms such as itching and tearing. This condition is commonly observed in young adults and is closely associated with environmental allergen exposure and genetic predisposition. This case report describes a 25 year old woman who presented with recurrent nasal obstruction for the past four years. The symptoms were more pronounced in the morning and during exposure to cold air. The patient also reported repetitive sneezing episodes, occurring 10 to 15 times after exposure to dust, accompanied by clear rhinorrhea, nasal and ocular itching, and a habitual nose rubbing behavior. Ocular complaints, including watery and itchy eyes, were consistently reported. Physical examination revealed livid discoloration of the nasal cavity mucosa and septum. The inferior turbinates appeared edematous and hyperemic with clear nasal secretions. No septal deviation or signs of acute infection were observed. Based on the persistence of symptoms for more than four weeks and the characteristic clinical findings, the patient was diagnosed with mild persistent allergic rhinitis. Management included oral antihistamine therapy with cetirizine, a nasal decongestant containing pseudoephedrine hydrochloride, and intranasal corticosteroid therapy with fluticasone furoate. In addition to pharmacological treatment, the patient received education on allergen avoidance, adoption of healthy lifestyle practices, and regular physical activity. This case highlights the importance of recognizing long term symptoms, performing a thorough physical examination, and applying an appropriate combination of pharmacological and non pharmacological interventions to achieve symptom control, improve quality of life, and prevent disease progression in patients with allergic rhinitis.